Values integration across curriculum in the K to 12 program: repository - Alabado, Irene M.; Carabeo, Jordan M.; Antionio, Ella Mae O.; Enchano, Paula Angelu E. (Paranaque City: Olivarez College, 2020)
In learning, it is not only important to learn the basic knowledge and skills which are necessary for seeking a future occupation but rather, education and the process of learning is also concerned with teaching the importance of values in students' lives and the significant role it will play in their future and as well as in their development as a person. This present study had analyzed the integration of values in the three academic subjects - English, Science, and Mathematics of 48 students and three subject teachers from Parañaque Central Elementary School as well as their views and perception on the extent and effectiveness of values integration in English, Science, and Math subjects, how does values integration impact student development, what are the challenges encountered by the respondents in integrating values in such subjects; the significant difference and relationship among the extent, effectiveness and impact of values integration in the three academic subjects; and finally, what values integrated lesson exemplars can be designed as intended for English, Science, and Mathematics subjects The data regarding the analysis of values integration in the three subject areas were presented and analyzed through quantitative descriptive weighted mean while correlation in terms of significant difference and relationship among the extent, effectiveness, and impact of values integration in the three academic subjects. There are moderate positive correlations were calculated between the extent and impact of values integration and effectiveness of values integration and impact of values integration.
Undergraduate thesis.
Keywords: Values integration; Academic subjects; Student development; Lesson exemplar; Repository